Caring Leadership in Schools: Findings From Exploratory Analyses. (April 2016) - Louis, Karen Seashore; Murphy, Joseph; Smylie, Mark
Purpose: This article (1) analyzes and synthesizes literatures from philosophy and education to propose a conceptual framework for caring in schools and caring school leadership and (2) reports the results of an exploratory analysis of the relationship of caring principal leadership to school-level supports for student academic learning.Conceptual Framework: This conceptual framework defines caring as a quality of social relationships with several core elements: attentiveness and authentic knowledge of others, motivational displacement, situationality, mutuality, and authenticity. Characteristics of relationships and organizational conditions that enable caring and caring leadership are proposed.Research Design: The empirical analysis employs a survey of teachers in 134 schools. Measures of principal caring and student academic support were developed and related to the conceptual framework and student achievement using regression and path analyses.Findings: We found significant positive relationships among caring principal leadership, student academic support, and teachers' sense of collective responsibility. In addition, small but significant relationships of caring principal leadership with student academic support and teachers' collective responsibility to student achievement were apparent. Caring leadership has an indirect relationship to student achievement through student academic support.Conclusions: This article makes a case for the importance of caring and caring school leadership for the success and well-being of both teachers and students in schools. While the work is exploratory, it points in promising directions for further theory building, research, and development of leadership practice.